Discharge Identity of Medullary Inspiratory Neurons is Altered during Repetitive Fictive Cough - Segers, Lauren S.; Nuding, Sarah C.; Vovk, Andrea; Pitts, Teresa; Baekey, David M.; O'Connor, Russell; Morris, Kendall F.; Lindsey, Bruce G.; Shannon, Roger; Bolser, Donald C. (Frontiers in Physiology, 2012)
This study investigated the stability of the discharge identity of inspiratory decrementing (I Dec) and augmenting (I Aug) neurons in the caudal (cVRC) and rostral (rVRC) ventral respiratory column during repetitive fictive cough in the cat. Inspiratory neurons in the cVRC (n = 23) and rVRC (n = 17) were recorded with microelectrodes. Fictive cough was elicited by mechanical stimulation of the intrathoracic trachea. Approximately 43% (10 of 23) of I Dec neurons shifted to an augmenting discharge pattern during the first cough cycle (C1). By the second cough cycle (C2), half of these returned to a decrementing pattern. Approximately 94% (16 of 17) of I Aug neurons retained an augmenting pattern during C1 of a multi-cough response episode. Phrenic burst amplitude and inspiratory duration increased during C1, but decreased with each subsequent cough in a series of repetitive coughs. As a step in evaluating the model-driven hypothesis that VRC I-Dec neurons contribute to the augmentation of inspiratory drive during cough via inhibition of VRC tonic expiratory neurons that inhibit premotor inspiratory neurons, cross-correlation analysis was used to assess relationships of tonic expiratory cells with simultaneously recorded inspiratory neurons. Our results suggest that reconfiguration of inspiratory-related sub-networks of the respiratory pattern generator occurs on a cycle by cycle basis during repetitive coughing.